EFEKTIVITAS PENGENALAN IKON BARU UNTAG SURABAYA KEPADA MAHASISWA DAN DOSEN UNTAG SURABAYA - Sayyidah, Rahmawati; Sudaryanto, Edy; Jupriono, Jupriono (representamen, 2015)
17 August University of Surabaya is the oldest private university in Surabaya . established by thefoundation universities August 17, 1945 Surabaya abbreviated YPTA . Consists of structural foundationsas the founder of the foundation and structural University of the implementing agency in the activitiesthat occurred at the University . As one of the university in charge of public relations function inproviding information and related publications UNTAG Surabaya . PR has just launched a new iconUNTAG Surabaya as a tool related publications UNTAG Surabaya . This icon was made in order to helpthe public relations work . Effective communication can help increase public relations job in conveyingall kinds of relevant information on public UNTAG Surabaya either Internal or External . Formulation ofthe problem in this research is " How can the effectiveness of the introduction of new icons UNTAGSurabaya in Surabaya Students and Lecturers UNTAG?" . This study used quantitative descriptivemethod by distributing questionnaires to a sample withdrawal . Sample in this study is the Student andLecturer UNTAG Surabaya . From this study , the authors would like to explain that the effectiveness ofthe introduction of new icons UNTAG Surabaya can support and assist the activities of PR in conveyingrelevant information UNTAG Surabaya.Keywords: effectiveness, communication, icons, students, professors .